Implementasi Program Pengelolaan Dana Bantuan Operasional Satuan Pendidikan Di Sekolah Menengah Pertama Negeri 1 Sekadau Hilir Kabupaten Sekadau Tahun 2024 - Rosalena; Martoyo; Arifin (LPPM STISIP IMAM BONJOL, 2026)
The purpose of this study is to determine and analyze the implementation process of the BOSP (Bantuan Operasional Satuan Pendidikan) Fund Management Program at SMPN 1 Sekadau Hilir, Sekadau Regency in 2024, examined through the aspects of policy effectiveness accuracy, implementation accuracy, target accuracy, and environmental accuracy. The research method used a descriptive qualitative approach. The results of the study show that, in general, the BOSP Fund management at SMPN 1 Sekadau Hilir has been carried out according to the guidelines, but several constraints were still found, such as the suboptimal utilization of the previous year's remaining balance, the lack of stakeholder involvement in planning, and limited facilities and infrastructure that affect the effectiveness of program implementation.